DIAGNOSTIC METHODS IN AYURVEDA - Thakar, V. J. (Medknow Publications & Media Pvt Ltd, 1982)
This is an analytical study of the Diagnostic methods Prescribes in Ayurveda. As in the case of disease and treatments the concept of diagnosis also is unique in Ayurveda. It goes to the Nidana of Doshicimbalance by studying the physical, physiological, psychic and behavoural aspects of the patient. The paper gives an insight into the various diagnostic methods enunciated in Sastras which turns out to be a fore-runner of any of modern diagnostic methods.